2021
DOI: 10.1055/s-0041-1735274
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Leak after Ileal Pouch–Anal Anastomosis

Abstract: There are special considerations when treating anastomotic leak after restorative proctocolectomy and ileal pouch–anal anastomosis. The epidemiology, risk factors, anatomic considerations, diagnosis and management, as well as the short- and long-term consequences to the patient are unique to this patent population. Additionally, there are specific concerns such as “tip of the J” leaks, transanal management of anastomotic leak/presacral sinus, functional outcomes after leak, and considerations of redo pouch pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Up to 15% of ileoanal pouches will develop a symptomatic leak [ 6 ]. The clinical presentation is driven by the timing of the leak.…”
Section: Methodsmentioning
confidence: 99%
“…Up to 15% of ileoanal pouches will develop a symptomatic leak [ 6 ]. The clinical presentation is driven by the timing of the leak.…”
Section: Methodsmentioning
confidence: 99%
“…According to Guyton et al, the reported rates of anastomotic leak following ileal pouch-anal anastomosis (IPAA) vary widely from 5% to 19%, with the majority of this contributing data coming from single institution case series [ 1 ]. Following an uncontrolled leak discovery, the goals of treatment are patient resuscitation and infection source control.…”
Section: Introductionmentioning
confidence: 99%